Challenges of Sustainable Development of TVET Programs and Projects (Journal of Training and Development, 2016)
Education is a key to open the door of human development and TVET is master key to open the door of economic development of the world. Therefore, all most all countries have given high priority for TVET to empower their human capital and economic development. Despite their initiatives, majority of them could not achieve sustainable development of TVET. There are different challenges and issues that are hindering on it. This paper describes on brief introduction on sustainable development and sustainable TVET or green TVET. It also highlights the major challenges of sustainable development of TVET.